First isolation and characterization of a bovine parainfluenza virus type 3 genotype C strain from an aborted Holstein fetus - Ren, Yunxin; Chen, Xi; Tang, Cheng; Yue, Hua (Frontiers in Veterinary Science, 2025)
Bovine parainfluenza virus type 3 (BPIV3) is a significant pathogen responsible for bovine respiratory disease complex (BRDC) and reproductive disorders. Despite its importance, genomic studies of BPIV3 in abortion samples are currently lacking. We detected a BPIV3-positive sample via PCR in the lung sample from an aborted Holstein fetus; therefore, this study aimed to isolate and identify a BPIV3 strain from the aborted fetus sample of Holstein and analyze its genome. We successfully isolated and obtained a BPIV3 strain using MDBK cell lines, named LC1. Phylogenetic analysis based on complete genome sequences revealed that the LC1 strain belongs to genotype C and clusters into a branch with the Chinese strain SD2020. Notably, unique amino acid mutations were identified in the P (I297T) and M (P5N) proteins of the LC1 strain. To the best of our knowledge, this is the first BPIV3 genotype C strain to be isolated from a bovine abortion sample, as well as the first characterization of the abortion source BPIV3 genome reported. This finding lays the foundation for further studies on the genetic diversity of BPIV3.